An Investigation into the Body Mass Index Levels of Female University Students and Women from Different Ages - İskender Güler (Journal of Educational Issues, 2024)
The purpose of this study was to determine and to evaluate the Body Mass Index (BMI) levels of female students between the ages of 20 and 30 who study at Amasya University and women between the ages of 40 and 60 who live in Amasya since BMI levels are of great importance to determine the body fat levels for a healthy body. We recruited 910 female students and 688 women. All participants had no health problems. The formula we used for BMI levels of the participants was BMI = kg/m2. We relied on such parameters as mean, standart deviation, minimum and maximum values for statistical analyses of the data. We conducted the independent samples t test to see if there was any statistically significant differences between groups. The findings showed that female university students’ body mass index levels were 21.84 kg/m2, while women living in Amasya had 27.68 kg/m2 body mass index levels. We found a statistically significant difference in the body mass index levels between the groups in favor of the female university students. We conclude that female university students between the ages of 20 and 30 who study at Amasya University had normal levels of BMI when compared with women between the ages of 40 and 60 who live in Amasya.